GAMBARAN IBU BERSALIN DENGAN OLIGOHIDRAMION DI RUMAH SAKIT BERSALIN PERMATA HATI KOTA METRO - Hidayati, Nurma (Jurnal Kesehatan, 2022)
Oligohydramion is a condition when there is very little amionic fluid. This condition occurs due to uteroplasm efficiency. The cause of oligohydramion is not yet clear, but this condition is not good for fetal growth because fetal growth can be disrupted by adhesions of the fetal skin and amion or because the fetus is under pressure from the uterine wall. The purpose of this study was to determine the description of mothers giving birth with oligohydramion at the Permata Hati Maternity Hospital in Metro City in 2021. This research is descriptive in nature, the research subject is a woman giving birth with oligohydramion, while the object of the research is a description of a woman giving birth with oligohydramion. The population in this study were 74 people and all of the population were sampled. The data collection tool used in this research is a checklist taken from secondary data (RM) and the data analysis uses univariate analysis using frequency distribution. The results showed that the majority of pregnant women who experienced oligohydramion at the Permata Hati Maternity Hospital in the city of metro in 2021 were at term, 47 respondents (63.5%) types of artificial labor (SC) 66 respondents (89.2%) babies who were given birth control. gave birth without asphyxia 58 respondents (73.3%) no hypertension 69 respondents (93%). The conclusion of this study showed that women who gave birth with oligohydramion at Permata Hati Hospital, Metro City in 2021, the majority of mothers gave birth at term gestation, artificial delivery (SC), babies were not asphyxia, no hypertension, therefore it is recommended to be evaluated and considered to improve health services for pregnant women, maternity and newborns (BBL), especially with mothers who experience oligohydramion and reduce the incidence of oligohydramion by performing ultrasound examinations on pregnant women who make ANC visits.Keywords: Oligohydramion, Gestational Age, Type of Delivery, Type of Asphyxia, Hypertension